2009
DOI: 10.1021/cm803329w
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Growth of Nanocrystalline Mn-Doped ZnS Thin Films Prepared by Chemical Bath Deposition and Optical Properties

Abstract: ZnS:Mn thin films were deposited on quartz, Si (polycrystalline), and glass substrates using a chemical bath deposition (CBD) method in an aqueous solution containing ethylene diamine tetra acetic acid disodium salt (Na 2 EDTA) as the complexing agent for zinc ions and thioacetamide (TAA) as the sulfide source at temperatures ranging from 50 to 80 °C. ZnS:Mn thin films with thicknesses ranging from 60 to 450 nm were synthesized at various Mn 2+ /Zn 2+ molar ratios ranging from 1 to 4. The effects of the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
33
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(35 citation statements)
references
References 63 publications
0
33
0
Order By: Relevance
“…Increase of Cu 2+ concentration has been reported to result in quenching of luminescence due to formation of CuS 18 . Doping with Mn has been reported to give highly transparent ZnS film along with quantum size effect 19 . Quantum confinement was also reported Mn doped ZnS thin films prepared by spin coating 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Increase of Cu 2+ concentration has been reported to result in quenching of luminescence due to formation of CuS 18 . Doping with Mn has been reported to give highly transparent ZnS film along with quantum size effect 19 . Quantum confinement was also reported Mn doped ZnS thin films prepared by spin coating 5 .…”
Section: Introductionmentioning
confidence: 99%
“…Morever, the UV emission band has a trend to be quenched. The blue emission band at around 442 nm is attributed to the surface defects such as sulfur vacancy or sulfur interstitial lattice defects [2,3,5]. Meanwhile, the green emission at around 520 nm may be assigned to the surface defects such as oxygen vacancies [16].…”
Section: Resultsmentioning
confidence: 99%
“… ZnS, an II-VI semiconductor, has been extensively investigated due to its potential applications in optics, photoelectronics, sensors, catalysts and so on [1][2][3]. Recently, numerous efforts have been employed to control the fabrication of micro and nanomaterials with various morphologies, since the novel properties and potential applications of nanomaterials depend sensitively on their shapes and sizes [4].…”
Section: Introductionmentioning
confidence: 99%
“…Some of the different methods of compound immobilization and electrode functionalization include spin coating, covalent attachment, and electropolymerization (Brown et al, 2002). This research focuses on the chemical modification of platinum electrodes via electropolymerization and characterization of the derived films using CV and RBS (Baum et al, 1991;Huang et al, 1992;Ramana et al, 2005;Lee et al, 2006;Walters et al, 2008;Goudarzi et al, 2009;Niesen et al, 2001). Several research groups have reported on the electropolymerization of tris(5-amino-1,10-phenanthroline) iron(II) and ruthenium(II) complexes (Ellis et al, 1983;Ren et al, 1994); platinum electrodes used in our work have been modified with a ruthenium complex of 5-amino-1,10-phenanthroline, (Ru(5-phenNH 2 ) 3 )(PF 6 ) 2 .…”
Section: Introductionmentioning
confidence: 99%